Revolutionizing Financial Risk Management: Blockchain's Role in Transforming Global Banking Systems - Syarkani, Yofi; Subu, Muhammad Arsyad; Waluyo, Imam (Indonesian Scientific Publication, 2024)
The rapid advancement of digital technologies has revolutionized global banking, with blockchain technology emerging as a transformative tool for financial risk management. Its decentralized, immutable, and transparent framework offers fraud prevention, operational risk mitigation, and enhanced regulatory compliance benefits. However, its role in addressing pandemic-induced uncertainties and complex risk management challenges remains insufficiently explored. This study aims to analyze blockchain's transformative role in financial risk management within global banking, focusing on its adoption during and after the COVID-19 pandemic. Method: Using a Systematic Literature Review (SLR) methodology, the research synthesizes findings from peer-reviewed articles and industry reports published between 2018 and 2024.The results reveal that blockchain reduces fraud risks through immutable records, improves operational efficiency via smart contracts, and enhances compliance with Know Your Customer (KYC) and Anti-Money Laundering (AML) regulations. It also strengthens resilience by mitigating risks from central system failures and enabling real-time monitoring of financial transactions. Despite these advantages, challenges like scalability issues and fragmented global regulations limit its adoption. During the pandemic, blockchain demonstrated its crisis-resilient potential by enabling secure online transactions and real-time fraud detection. The study concludes that blockchain offers transformative benefits for financial risk management. However, its broader adoption requires strategic interventions, such as unified regulatory frameworks, scalability solutions, and sandbox environments to foster innovation. Addressing these challenges could unlock blockchain’s full potential in reshaping global banking with enhanced transparency.